“Palashaˮ A Curative Medicine in Diabetes Mellitus - Gupta, Abhishek; Kumar, Arun; Upadhyay, Vishal (International Research Journal of Ayurveda & Yoga, 2021)
Diabetes mellitus is a worldwide grave health problem challenging physicians globally. There are many factors that play role in the development of this disease, including environment, nutrition infection, genetic predisposition and side effect of modern drugs. Ayurveda refers to Diabetes mellitus as ―Madhumeha. Among the Ayurvedic texts Charka[1] , Vagbhata and Madhava have brought the word Madhumeha into use while, naming 20 subtypes of Prameha whereas Susruta has used the word Ksaudrameha. Madhu, and Ksaudra are literally synonyms of each other. But at a different place, Madhumeha‘ too has been used and Susruta has devoted one complete chapter to the treatment of Madhumeha. He has accepted Madhumeha to be the stage of complications of Prameha. If only the literal meaning of the words is to be seen Madhumeha‘ is the appropriate term for diabetes mellitus. The selected drug Palasha (Butea monosperma Linn. Kuntz) possesses Tikta, Kashaya rasa and has Pramehaghna properties and actions, therefore drug seems to be rational for treatment of Madhumeha. Palasha was proved to be useful and harmless remedy for Madhumeha. Today, it is a challenge for scientists to provide efficient, safe and cheap medications. In this scenario, Palasha can be an exclusive medicine which is widely available throughout country.